2022
DOI: 10.1155/2022/1666792
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Correlation between N7-Methylguanosine Modification-Related lncRNAs and Survival Prognosis of Oral Squamous Cell Carcinoma Based on Comprehensive Bioinformatics Analysis

Abstract: Objective. N7-methylguanosine modification-related lncRNAs (m7G-related lncRNAs) are involved in progression of many diseases. This study was aimed at revealing the risk correlation between N7-methylguanosine modification-related lncRNAs and survival prognosis of oral squamous cell carcinoma. Methods. In the present study, coexpression network analysis and univariate Cox analysis were used to obtained 31 m7G-related mRNAs and 399 m7G-related lncRNAs. And the prognostic risk score model of OSCC patients was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Although some differentially expressed genes were shared between T2D and control samples ( Figure 3 B), 181 up- and 179 down-regulated genes were differentially regulated specifically in T2D compared to the control samples, including 35 up- and 22 down-regulated lncRNA genes ( Supplementary Table S6 ). Among these up-regulated lncRNA genes, only the following nine have been previously studied: (1) ENSG00000232855 (novel transcript) [ 75 ]; (2) ENSG00000272512 (novel transcript) [ 76 ]; (3) KCNJ2 antisense RNA 1 (KCNJ2-AS1) [ 77 , 78 , 79 ]; (4) KLHDC7B divergent transcript (KLHDC7B-DT) [ 80 , 81 , 82 ]; (5) long intergenic non-protein-coding RNA 2015 (LINC02015) [ 83 , 84 ]; (6) long intergenic non-protein-coding RNA 2381 (LINC02381) [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; (7) long intergenic non-protein-coding RNA 2541 (LINC02541) [ 94 ]; (8) serpin family B member 9 pseudogene 1 (SERPINB9P1) [ 95 , 96 , 97 ]; and (9) USP30 antisense RNA 1 (USP30-AS1) [ 98 , 99 , 100 ]. However, only the functions of the lncRNA genes LINC02381 and USP30_AS1 are known, with the former known to bind transcription factors [ 85 ], RNA-binding proteins [ 86 ], and miRNAs [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; while USP30-AS1 acts as a miRNA sponge [ 98 , 99 ] and is involved in the cis-regulation of the nearby protein-coding genes USP30 and ANKRD13A [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some differentially expressed genes were shared between T2D and control samples ( Figure 3 B), 181 up- and 179 down-regulated genes were differentially regulated specifically in T2D compared to the control samples, including 35 up- and 22 down-regulated lncRNA genes ( Supplementary Table S6 ). Among these up-regulated lncRNA genes, only the following nine have been previously studied: (1) ENSG00000232855 (novel transcript) [ 75 ]; (2) ENSG00000272512 (novel transcript) [ 76 ]; (3) KCNJ2 antisense RNA 1 (KCNJ2-AS1) [ 77 , 78 , 79 ]; (4) KLHDC7B divergent transcript (KLHDC7B-DT) [ 80 , 81 , 82 ]; (5) long intergenic non-protein-coding RNA 2015 (LINC02015) [ 83 , 84 ]; (6) long intergenic non-protein-coding RNA 2381 (LINC02381) [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; (7) long intergenic non-protein-coding RNA 2541 (LINC02541) [ 94 ]; (8) serpin family B member 9 pseudogene 1 (SERPINB9P1) [ 95 , 96 , 97 ]; and (9) USP30 antisense RNA 1 (USP30-AS1) [ 98 , 99 , 100 ]. However, only the functions of the lncRNA genes LINC02381 and USP30_AS1 are known, with the former known to bind transcription factors [ 85 ], RNA-binding proteins [ 86 ], and miRNAs [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; while USP30-AS1 acts as a miRNA sponge [ 98 , 99 ] and is involved in the cis-regulation of the nearby protein-coding genes USP30 and ANKRD13A [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2) ENSG00000272512 (novel transcript) [76]; (3) KCNJ2 antisense RNA 1 (KCNJ2-AS1) [77][78][79]; (4) KLHDC7B divergent transcript (KLHDC7B-DT) [80][81][82]; (5) long intergenic non-proteincoding RNA 2015 (LINC02015) [83,84]; (6) long intergenic non-protein-coding RNA 2381 (LINC02381) [85][86][87][88][89][90][91][92][93]; (7) long intergenic non-protein-coding RNA 2541 (LINC02541) [94]; (8) serpin family B member 9 pseudogene 1 (SERPINB9P1) [95][96][97]; and (9) USP30 antisense RNA 1 (USP30-AS1) [98][99][100]. However, only the functions of the lncRNA genes LINC02381 and USP30_AS1 are known, with the former known to bind transcription factors [85], RNA-binding proteins [86], and miRNAs [87][88][89][90][91][92][93]; while USP30-AS1 acts as a miRNA sponge [98,99] and is involved in the cis-regulation of the nearby protein-coding genes USP30 and ANKRD13A [100].…”
Section: Many Lncrnas Are Differentially Expressed In Cultured Macrop...mentioning
confidence: 99%
“…Further evidence suggests that FENDRR acts as a miRNA sponge for miR-214-3p, thereby suppressing the progression of gastric cancer [23]. Moreover, AL513550.1 has been implicated in elucidating the link between survival prognosis and N7-methylguanosine modification-related lncRNAs in oral squamous cell carcinoma [24]. Similarly, ATP2A1-AS1 has emerged as a promising prognostic biomarker for patients with cervical cancer [25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the application of multimodal treatment including surgery, radiation therapy, chemotherapy, targeted molecular therapy, and immunotherapy, the 5-year survival rate is still relatively low [15]. A previous study reported that AC005332.6 was an independent prognostic factor for oral squamous cell carcinoma based on bio-informatics analysis [22]. Additionally, LINC02747 had been explored to play an essential role in clear cell renal cell carcinoma (ccRCC).…”
Section: Discussionmentioning
confidence: 99%